Influência da telemedicina na qualidade de vida de pacientes em cuidados paliativos - Matte, Everson Liz Allet (2021)
The Evolution of health care in recent decades has led to a longer life expectancy in the world. The decrease in mortality from infectious diseases has led to an increase in the incidence of non-reportable diseases, such as atherosclerotic and neoplastic diseases, with a proportional increase in such entities as a cause of mortality in the population of developed countries. A significant part of these patients may have great suffering as result of both the disease and the treatment, without significant improvement in the survival time. Palliative Care (CP) is a treatment modality aimed at controlling symptoms in patients with life threatening diseases, improving the quality of life in adults and children. The use of communication technology in health, named Telemedicine, has become increasingly common as it is cheaper and more accessible. Telemedicine, as a biotechnological tool, can improve health care in the most diverse medical specialties. The objective of this dissertation is to evaluate the effectiveness of the telemedicine systems applied to palliative care patients in relation to quality of life and symptom control through systematic review of the literature. A search was performed in the MEDLINE, CENTRAL, Scopus, Scielo, Lilacs and OpenGrey databases, in addition to a search in the databases of clinical studies under development (clinicaltrials.gov). The identified records were selected, through the reading of the title and summary, those that address the use of telemedicine in patients with advanced chronic diseases eligible for CP who aimed to assess quality of life or symptom control were considered eligible. These articles were read in full. Thirteen articles met the inclusion criteria. They were synthesized according to the types of patients, types of intervention, comparison group and measured results. We have identified a tendency to improve the quality of life in patients undergoing telemedicine programs, especially the quality of mental life. There was no difference in the need to use hospital resources. Telemedicine is applicable to PC patients and can complement face-to-face care, especially in places that are difficult to access. However, larger multicenter studies focusing on costeffectiveness are needed to define whether it can be less costly for funders of the health system than conventional treatment.